(untitled) (Multidisciplinary Journal of Science and Technology, 2023)
this article describes the concept and evolution of money supply of military personnel. In addition, the nature, principles, functions and structure of military allowances are analyzed. In addition, the evolution of the payment system for military personnel is covered in detail.